(untitled) - Shearer, Findlay (Amsterdam,London, 2008)
Need more power from your mobile device.
Keywords: Electronic digital computers,Wireless communication systems,Personal communication service systems,Máy tính điện tử kỹ thuật số,Hệ thống truyền thông không dây,Hệ thống dịch vụ truyền thông cá nhân; Power supply,Power supply,Power supply,Nguồn cung cấp,Nguồn cung cấp,Nguồn cung cấp